Partial genomic characterization on potentially new bacteriophage: New addition to ICTV database? - Dharmela Sellvam; Yahya Mat Arip (Syiah Kuala University, 2012)
A small infectious micro-organism that able to replicate only inside the living cells is named as viruses, which are also the most abundant life form on the earth. These subcellular organisms can be classified into four groups ; animal, plant, archaea and bacteria viruses. Among them, bacteria viruses or also known as bacteriophages have the highest numbers with the total estimation of 1031 . The fact is that, until today only 6,000 types of phages have been discovered since 1959 (ICTV report, 2011). Therefore, there are lots of new phages waiting to be discovered. Partial genomic studies have been conducted on a potential new bacteriophage isolated from goat faeces. Thus, to fulfil the objective of this study genomic characterization was carried out to discover more genomic details in order to reveal the true identity of the newly isolated phage . As first part of the analysis, phage genome was extracted to identify the phage's genome type and to estimate the genome size. Along with that, the extracted genome was used to proceed with the genome profiling and also for partial genome sequencing analysis. Based on the genomic analysis, the results showed the isolated phage carries DNA as it genetic material with the size of genome around 30-40kbp. Besides that, this phage produced different genomic profile in comparison with other known phages such as Lambda, T4 and T7 phages when digest with the same restriction enzymes. Besides that, based on partial genome sequencing and results run against NCBI database, this newly isolated phage might be related with another newly isolated phage known as Sodalis phage SO-1. As far as the genomic data collected, an assumption can be made that this isolated phage could be a new addition to the list of viruses in International Committee on Taxonomy of Viruses (ICTV) database.